2021
DOI: 10.3390/polym13010156
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Unfolding and Aggregation near a Hydrophobic Interface

Abstract: The behavior of proteins near interfaces is relevant for biological and medical purposes. Previous results in bulk show that, when the protein concentration increases, the proteins unfold and, at higher concentrations, aggregate. Here, we study how the presence of a hydrophobic surface affects this course of events. To this goal, we use a coarse-grained model of proteins and study by simulations their folding and aggregation near an ideal hydrophobic surface in an aqueous environment by changing parameters suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
0
36
0
Order By: Relevance
“…The thin layer of water that directly hydrates the membrane, commonly referred to as biological water, , has been proven to actively participate in the biological functioning of DNA . Moreover, biological water is inherently connected with the process of protein folding, aggregation, , and stabilization of the structure even in extreme thermodynamic conditions . Numerous experiments aimed at understanding the properties of biological water, using nuclear magnetic resonance, X-ray and neutron scattering, , infrared spectroscopy, sum frequency generation, , and molecular dynamics simulations, among others, showed that water molecules form a network structure, being bound by hydrogen bonds and weak van der Waals interactions around the polar head group, the so-called clathrate hydration structure .…”
Section: Introductionmentioning
confidence: 99%
“…The thin layer of water that directly hydrates the membrane, commonly referred to as biological water, , has been proven to actively participate in the biological functioning of DNA . Moreover, biological water is inherently connected with the process of protein folding, aggregation, , and stabilization of the structure even in extreme thermodynamic conditions . Numerous experiments aimed at understanding the properties of biological water, using nuclear magnetic resonance, X-ray and neutron scattering, , infrared spectroscopy, sum frequency generation, , and molecular dynamics simulations, among others, showed that water molecules form a network structure, being bound by hydrogen bonds and weak van der Waals interactions around the polar head group, the so-called clathrate hydration structure .…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous media, proteins undergo many physicochemical changes such as conformational alterations, denaturation, folding/unfolding processes, and ligand exchange [1][2][3][4][5][6]. These phenomena can be invoked by variations in the temperature and/or the pH of a solution.…”
Section: Introductionmentioning
confidence: 99%
“…If a protein has a hydrophobic side chain, it may adsorb onto lipid bilayer membranes (Arbuzova et al, 1998). Protein adsorption and denaturation at interfaces such as water/oil or water/air is a widely recognized phenomenon (March et al, 2021).…”
Section: Macromolecular Confinement and Adsorptionmentioning
confidence: 99%